2007
DOI: 10.1177/1359105307074267
|View full text |Cite
|
Sign up to set email alerts
|

A Self-determination Theory Approach to the Study of Body Image Concerns, Self-presentation and Self-perceptions in a Sample of Aerobic Instructors

Abstract: This study examined motivational predictors of body image concerns, self-presentation and self-perceptions using self-determination theory (Deci & Ryan, 1985) as a guiding framework. Aerobic instructors (N = 149) completed questionnaires measuring general need satisfaction, exercise motivational regulations, body image concerns, social physique anxiety, and self-perceptions. Introjected regulation predicted all outcome variables in the expected direction. Intrinsic motivation positively predicted physical self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
1
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 48 publications
5
56
1
8
Order By: Relevance
“…Parcelling is used with unidimensional scales as a means of increasing the stability of parameter estimates and keeping an acceptable ratio of sample size to estimated parameters in studies involving relatively low sample sizes (Bandalos & Finney, 2001). largely supportive of the model and our hypotheses and were aligned with previous related work (e.g., Pelletier & Dion, 2007;Thøgersen-Ntoumani & Ntoumanis, 2007). Specifically, we found basic need psychological satisfaction to be a direct negative predictor of body image concerns (as indicated by drive for thinness and body dissatisfaction), and an indirect negative predictor of unhealthy weight control behaviours (e.g., skipping meals, fasting).…”
Section: Preliminary Analysessupporting
confidence: 72%
See 1 more Smart Citation
“…Parcelling is used with unidimensional scales as a means of increasing the stability of parameter estimates and keeping an acceptable ratio of sample size to estimated parameters in studies involving relatively low sample sizes (Bandalos & Finney, 2001). largely supportive of the model and our hypotheses and were aligned with previous related work (e.g., Pelletier & Dion, 2007;Thøgersen-Ntoumani & Ntoumanis, 2007). Specifically, we found basic need psychological satisfaction to be a direct negative predictor of body image concerns (as indicated by drive for thinness and body dissatisfaction), and an indirect negative predictor of unhealthy weight control behaviours (e.g., skipping meals, fasting).…”
Section: Preliminary Analysessupporting
confidence: 72%
“…For example, women's level of autonomy in their lives appears to protect against body image pressures (Pelletier & Dion, 2007) and is negatively associated with bulimic behaviours (Pelletier, Dion, & Lévesque, 2004). Further, in a sample of (mainly female) aerobics instructors, general autonomy need satisfaction was found to negatively predict body image concerns (i.e., body dissatisfaction and drive for thinness; Thøgersen-Ntoumani & Ntoumanis, 2007). Although such evidence is cross-sectional in nature, it suggests the possibility that perceptions of control over one's life may be important in protecting against the development of body image concerns.…”
mentioning
confidence: 99%
“…A study by Strauss and Ryan (1987) showing that patients with anorexia nervosa reported a lack of autonomy and feelings of ineffectiveness supports the theoretical assumption that unfulfilled needs for autonomy and competence are associated with eating disorders. Meanwhile a series of studies supports the association between unfulfilled needs and problems associated with restricted eating (Pelletier et al 2004;Stok et al 2010;Thogersen-Ntoumani and Ntoumanis 2007).…”
Section: Unfulfilled Basic Needs and Eating Disordersmentioning
confidence: 99%
“…The few studies that have tested SDT in relation to body image variables have often focused on the drive for thinness in women (Thøgersen-Ntoumani & Ntomanis, 2007;Thøgersen-Ntoumani, Ntomanis, & Nikitaras, 2010). The role of SDT in men and muscularity remains to be examined.…”
mentioning
confidence: 99%